Quality Changes in White Sardine, Kowala cowl (Cuv.) during Frozen Storage - A.D., Serrao; G.G., Hiremath; K.C., Dora (Fishery Technology, 2025)
Experiments were conducted to evaluate the quality changes in white sardine Kowala coval (Cuv.) treated with BHA and ascorbic acid and sulphite during frozen storage at -20Â°C, for a period of 180 days. White sardine iced immediately after harvest and sub- sequently frozen within 6 to 8 h was in good condition over a period of 6 months at -20Â°C There was no significant difference in quality between the control, antioxidant treated and sulphite treated samples during storage.